Experimental study on the energy conversion of food waste via supercritical water gasification: Improvement of hydrogen production - Yan, Mi; Su, Hongcai; Hantoko, Dwi; Kanchanatip, Ekkachai; Hamid, Fauziah Shahul; Zhang, Sicheng; Wang, Guobin; Xu, Zhang (Elsevier, 2019)
In this study, the model food waste was gasified to hydrogen-rich syngas in a batch reactor under supercritical water condition. The model food consisted of rice, chicken, cabbage, and cooking oil. The effects of the main operating parameters including temperature (420–500 °C), residence time (20–60 min) and feedstock concentration (2–10 wt%) were investigated. Under the optimal condition at 500 °C, 2 wt% feedstock and 60 min residence time, the highest H 2 yield of 13.34 mol/kg and total gas yield of 28.27 mol/kg were obtained from non-catalytic experiments. In addition, four commercial catalysts namely FeCl 3 , K 2 CO 3 , activated carbon, and KOH were employed to investigate the catalytic effect of additives at the optimal condition. The results showed that the highest hydrogen yield of 20.37 mol/kg with H 2 selectivity of 113.19%, and the total gas yield of 38.36 mol/kg were achieved with 5 wt% KOH addition Moreover, the low heating value of gas products from catalytic experiments with KOH increased by 32.21% compared to the non-catalytic experiment. The catalytic performance of the catalysts can be ranked in descending order as KOH > activated carbon > FeCl 3 > K 2 CO 3 . The supercritical water gasification (SCWG) with KOH addition can be a potential applied technology for food waste treatment with production of hydrogen-rich gases. © 2019 Hydrogen Energy Publications LLC